2007
DOI: 10.4049/jimmunol.178.8.5058
|View full text |Cite
|
Sign up to set email alerts
|

Both the Suppressor of Cytokine Signaling 1 (SOCS-1) Kinase Inhibitory Region and SOCS-1 Mimetic Bind to JAK2 Autophosphorylation Site: Implications for the Development of a SOCS-1 Antagonist

Abstract: Suppressor of cytokine signaling (SOCS)-1 protein modulates signaling by IFN-γ by binding to the autophosphorylation site of JAK2 and by targeting bound JAK2 to the proteosome for degradation. We have developed a small tyrosine kinase inhibitor peptide (Tkip) that is a SOCS-1 mimetic. Tkip is compared in this study with the kinase inhibitory region (KIR) of SOCS-1 for JAK2 recognition, inhibition of kinase activity, and regulation of IFN-γ-induced biological activity. Tkip and a peptide corresponding to the KI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(141 citation statements)
references
References 32 publications
7
133
0
1
Order By: Relevance
“…SOCS1, via its SH2 domain, binds to Y1007 in the activation loop of JAK2. Originally identified as negative regulators of IL-6 signaling (Starr et al, 1997), subsequent studies have revealed that some SOCS proteins, such as SOCS1 and SOCS3, possess a kinase inhibitory region that is believed to compete with substrates of JAKs (reviewed in Khwaja, 2006) and peptides that correspond to this region can function as SOCS1 antagonists (Waiboci et al, 2007).…”
Section: Negative Regulation Of Janus Kinases-signal Transducers and mentioning
confidence: 99%
“…SOCS1, via its SH2 domain, binds to Y1007 in the activation loop of JAK2. Originally identified as negative regulators of IL-6 signaling (Starr et al, 1997), subsequent studies have revealed that some SOCS proteins, such as SOCS1 and SOCS3, possess a kinase inhibitory region that is believed to compete with substrates of JAKs (reviewed in Khwaja, 2006) and peptides that correspond to this region can function as SOCS1 antagonists (Waiboci et al, 2007).…”
Section: Negative Regulation Of Janus Kinases-signal Transducers and mentioning
confidence: 99%
“…Third, pJAK2(1001-1013) enhanced IFN-␥ activation of the luciferase reporter gene via the IFN-␥-activated sequence promoter element. Fourth, pJAK2(1001-1013) enhanced antigen-specific splenocyte proliferation (23). Subsequently, pJAK2(1001-1013) was reported to enhance antiviral immunity (24).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these findings, Waiboci and colleagues developed a small peptide antagonist of SOCS1, pJAK2(1001-1013), that corresponds to the activation loop of JAK2. Research results demonstrated that the pJAK2(1001-1013) peptide can block SOCS1-induced inhibition of STAT3 phosphorylation in IL-6-treated prostate cancer cells and enhance antigen-specific splenocyte proliferation (23). Later, they reported that, in addition to a direct antiviral effect and synergism with IFN-␥, the pJAK2(1001-1013) peptide exhibits adjuvant effects on humoral and cellular immunity, as well as an enhancement of polyinosinic-poly(C) activation of Toll-like receptor 3 (TLR3) (24).…”
mentioning
confidence: 99%
“…First, binding of a cytokine to its receptor upregulates expression of SOCS1. SOCS1 then inhibits JAK tyrosine kinase activity by binding to the catalytic site of Janus kinase tyrosine kinase (JAK), and by binding to and recruiting the ubiquitin-transferase complex to target JAK for proteasomal degradation [20,21]. SOCS1 also controls STAT and, indirectly, TLR signaling [22].…”
Section: Introductionmentioning
confidence: 99%